Instant Cement Forming Using Holt-Winter (case Study: CV Trijaya Abadi) - Devit Hari Firmanto; Eko Prasetyo; Mas Nurul Hamidah (Fakultas Teknik Universitas Bhayangkara, 2018)
CV.Trijaya Abadi is an industry that produces cement, and make various innovations by producing instant cement. Itis often the case with errors in doing the forecasting is if the amount of production is produced too much while thedemand is small it will cause losses for the company as well as vice versa if the demand a lot while the productionwill be a bit disappointment of consumers resulting in the company losing konsakuya. know the amount of instantcement production in the next period. The method used for forecasting in this research is Exponential SmoothingHolt-Winters method with multiplyative seasonal method and additive seasonal method. The alpha, beta and gammavalues used are 0.9, 0.1, and 0.1. With the value of these parameters are able to produce the value of MSEamounting to 52347.63 and MAPE value of 6,649 is forecasting in 2016 for multiplyative seasonal method. Foradditive seasonal method, the value of MSE is 50560.88 and MAPE value of 6,619 forecasting in 2016. So it isconcluded that it is more accurate to use the Holt-Winters additive seasonal method in 2016 forecasting of instantcement.